Saving a Legacy: Conservation of the paleontology resources within the Garden Park National Natural Landmark, Colorado, USA - Daniel Grenard; Kenneth Carpenter; Andrew Smith; Melissa Smeins (Geoconservation Research)
The Garden Park National Natural Landmark in central Colorado U.S.A. was established for 40 acres (0.16 sq. km) by the U.S. National Park Service in 1973 in recognition of its historical and paleontological significance. It was here that rather complete dinosaur skeletons were first discovered in great abundance and diversity in the late 1800s, sparking a growth in worldwide interest in dinosaurs. The dinosaur quarries played an important part in the "Bone Wars" in the early history of American paleontology. Despite the National Natural Landmark designation, human-caused environmental deterioration continued. Not until passage of the Federal Land Policy and Management Act (FLPMA) in 1976 did the Bureau of Land Management reassess the negative environmental impacts of public lands in Garden Park. A series of studies led to incremental protection of the environment and paleontological resources, beginning with the establishment of a Research Natural Area in 1987, then a larger Area of Critical Environmental Concern in 1996, and finally a greatly expanded National Natural Landmark in 2013. The multipurpose land usage mandated by FLPMA has at times resulted in conflicting goals in Garden Park. Over time, the local BLM has gradually increased protection of the paleontological resources, geological scenery and rare plants, while also providing educational and recreational opportunities.